Shared genetic etiology between alcohol dependence and major depressive disorder. (August 2018) - Foo, Jerome C.; Streit, Fabian; Treutlein, Jens; Ripke, Stephan; Witt, Stephanie H.; Strohmaier, Jana; Degenhardt, Franziska; Forstner, Andreas J.; Hoffmann, Per; Soyka, Michael; Dahmen, Norbert; Scherbaum, Norbert; et al.
Abstract : The clinical comorbidity of alcohol dependence (AD) and major depressive disorder (MDD) is well established, whereas genetic factors influencing co-occurrence remain unclear. A recent study using polygenic risk scores (PRS) calculated based on the first-wave Psychiatric Genomics Consortium MDD meta-analysis (PGC-MDD1) suggests a modest shared genetic contribution to MDD and AD. Using a (∼10 fold) larger discovery sample, we calculated PRS based on the second wave (PGC-MDD2) of results, in a severe AD case–control target sample. We found significant associations between AD disease status and MDD-PRS derived from both PGC-MDD2 (most informative P -threshold=1.0, P =0.00063, R 2 =0.533%) and PGC-MDD1 ( P -threshold=0.2, P =0.00014, R 2 =0.663%) meta-analyses; the larger discovery sample did not yield additional predictive power. In contrast, calculating PRS in a MDD target sample yielded increased power when using PGC-MDD2 ( P -threshold=1.0, P =0.000038, R 2 =1.34%) versus PGC-MDD1 ( P -threshold=1.0, P =0.0013, R 2 =0.81%). Furthermore, when calculating PGC-MDD2 PRS in a subsample of patients with AD recruited explicitly excluding comorbid MDD, significant associations were still found ( n =331; P -threshold=1.0, P =0.042, R 2 =0.398%). Meanwhile, in the subset of patients in which MDD was not the explicit exclusion criteria, PRS predicted more variance ( n =999; P -threshold=1.0, P =0.0003, R 2 =0.693%). Our findings replicate the reported genetic overlap between AD and MDD and also suggest the need for improved, rigorous phenotyping to identify true shared cross-disorder genetic factors. Larger target samples are needed to reduce noise and take advantage of increasing discovery sample size. Abstract : Supplemental Digital Content is available in the text.